2020
DOI: 10.3390/catal10080833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lanthanide-Functionalized Carbon Quantum Dots for Chemical Sensing and Photocatalytic Application

Abstract: Tunable photoluminescent-functionalized carbon quantum dots CQDs@Ln (TFA)3 (Ln = Eu, Tb; TFA: trifluoroacetylacetone) were designed and synthesized by introducing lanthanide complexes into the modified CQDs surface through the carboxyl group. The as-prepared CQDs@Ln (TFA)3 emit strong blue–green light with the peak at 435 nm and simultaneously show the characteristic emission of Ln3+ under irradiation of 365 nm light in aqueous solution. Moreover, these functionalized CQDs exhibit excellent photoluminescence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Figure S3B reveals the fluorescence emission spectrum of CDs at different excitation wavelengths ranging from 390 to 490 nm. It can be observed that the characteristic emission peaks do not shift with different excitation wavelengths, which illustrates that CDs show excitation independent photoluminescence behavior due to the similar surface states. , …”
Section: Resultsmentioning
confidence: 86%
“…Figure S3B reveals the fluorescence emission spectrum of CDs at different excitation wavelengths ranging from 390 to 490 nm. It can be observed that the characteristic emission peaks do not shift with different excitation wavelengths, which illustrates that CDs show excitation independent photoluminescence behavior due to the similar surface states. , …”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, lanthanide (Ln) elements have been extensively investigated across various application domains, including the display industry, magnets, bio-industry, pyroprocessing technology in nuclear power plants, and energy/environment fields [7][8][9][10][11][12][13][14][15][16]. Indeed, these elements exhibit unique physicochemical properties due to their unpaired 4f electronic configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide (Ln) elements have very usefully appeared in diverse application fields such as display industry, magnets, bio industry, pyroprocessing technology in nuclear power plants, and energy/environment fields [1][2][3][4][5][6][7][8][9][10]. The Ln elements have very unique and similar physicochemical properties because of electronic configurations in 4f-block in the periodic table.…”
Section: Introductionmentioning
confidence: 99%